Relationships between seminal plasma arginase activity and spermatological parameters in rams - Gur, S.; Kandemir, F. M. (Wiley-Blackwell, 2012)
This study was conducted to evaluate the correlation between seminal plasma arginase activity and spermatological parameters in rams. In this study, five fertility-proven Awassi rams were used as material. Six ejaculates were collected from each ram by an artificial vagina. Spermatological parameters (semen volume, mass activity, sperm motility and concentration and abnormal sperm rate) were immediately determined in each ejaculate. For enzyme assay, the semen samples were centrifuged and stored at -20 degrees C for the analysis of arginase activity. The average seminal plasma arginase activity was 0.61 +/- 0.20 U (mg protein)-1. There was a positive correlation between arginase activity and semen volume (r = 0.412, P < 0.05), semen mass activity (r = 0.610, P < 0.01), sperm motility (r = 0.447, P < 0.05) and sperm concentration (r = 0.808, P < 0.01). However, there was a negative correlation between arginase activity and abnormal sperm rate (r = -0.424, P < 0.05). In conclusion, this study clearly suggests that there is a significant correlation between seminal plasma arginase activity and spermatological parameters. In light of these results, seminal plasma arginase activity may be a biochemical criterion for determining sperm quality besides classical semen analysis parameters in rams.
Keywords: Arginase activity; ram; seminal plasma; spermatological parameters